TAREKAT DAN NASIONALISME: Kiprah Kebangsaan Jam‘iyyah Ahlith Thariqah Al-Mu - Mahzumi, Fikri; Muktafi, Muktafi; Yardho, Moh. (NALAR, 2025)
Sufism and nationalism are often perceived as opposing forces, with Sufism emphasizing spiritualism and nationalism focusing on materialism. However, in Indonesia, Sufism and its infrastructure have played a significant role, from the struggle for nationalism and the civil movement against colonialism to maintaining national unity after independence. Therefore, this article aims to examine the historicity of Sufism, particularly the role of tariqah organizations in shaping and sustaining nationalism in Indonesia. The article employs a qualitative study with a literature review approach. Data were sourced from the official websites of Jam'iyyah Ahlith Thariqah Al-Mu'tabarah An-Nahdliyyah (JATMAN) and Jam'iyyah Ahli Thoriqoh Mu'tabaroh Indonesia (JATMI), with articles, documents, and manuscripts selected based on their relevance and validity to the study's focus. The data were analyzed using the Miles and Huberman process, which involves data reduction, data display, and conclusion. Data analysis shows that in the phase before independence, Indonesian tariqah adherents were actively involved in promoting nationalism and the anti-colonialism movement in Indonesia. In parallel, during the phase following independence, nationalism was carried out in a more organized manner through two tariqah organizations, namely Jam'iyyah Ahlith Thariqah Al-Mu'tabarah An-Nahdliyyah (JATMAN) and Jam'iyyah Ahli Thoriqoh Mu'tabaroh Indonesia (JATMI). The nationalist role of these two tariqah organizations can be seen in the strengthening of religious moderation, character education, the internalization of spirituality in politics and leadership as support for the Unitary State of the Republic of Indonesia (NKRI) and the Pancasila ideology.